Percepção e experiência na criação poética - Thamos, Márcio [UNESP] (My University, 2010)
The artistic language is deeply related to the ability of imagination of the human spirit. The poetic experience is based on the perception of physical existence. The poet tries to show through images what he wishes to express and his tendency is to deal with words as a concrete thing.

A linguagem artística está profundamente relacionada à capacidade de imaginação do espírito humano. A experiência poética funda-se na percepção física da existência. O poeta busca dar a ver através de imagens aquilo que deseja exprimir e tende a valer-se da palavra como uma coisa em si.PALAVRAS-CHAVE: poesia, percepção sensorial, poeticidade, materialidade da palavra.ABSTRACT: The artistic language is deeply related to the ability of imagination of the human spirit. The poetic experience is based on the perception of physical existence. The poet tries to show through images what he wishes to express and his tendency is to deal with words as a concrete thing. KEYWORDS: poetry, sensory perception, materiality of the word.
Perception and experience in the poetic creation
Keywords: Poetry; Sensory Perception; Materiality of the Word; Poesia; Percepção Sensorial; Poeticidade; Materialidade da Palavra